Analisis Framing Berita Berjudul “Presiden Jakarta Selatan” di Majalah Tempo Edisi 22-28 April 2019 - Putra Perwira Guna Lubis; Leylia Khairani (Jurnal SOMASI (Sosial Humaniora Komunikasi), 2020)
The events of the Presidential Election in the United States in 2020 are similar to the political events of the 2019 Presidential Election in Indonesia, where Prabowo Subianto also claimed victory, accused of fraud, and also said he would sue the election results. If we look at the political events in 2019, the statement of Prabowo Subianto-Sandiaga Uno's victory claim as President and Vice President of the Republic of Indonesia for 2019-2024 on the same day after the election on April 17, 2019, has the potential to cause conflict. Moreover, coupled with the plan to create a “people power” movement which was interpreted as a way to win camp 02, the political situation in Indonesia was increasingly heated. So this research intends to see how the mass media, especially Tempo Magazine, which in 2019 framed issues related to Prabowo's victory claim. The object of this research is the news entitled "President of South Jakarta" which is published in the Main Report of Tempo Magazine, 22-28 April 2019 edition. This news was chosen because it is news that provides a unique description of the claim for victory in the 2019 Presidential Election voting results. used is the framing analysis model developed by Robert N. Entman. By using these analytical tools, it can be concluded that Tempo Magazine presents a problem definition that Prabowo is an actor who is the source of the problem because he feels superior in the 2019 Presidential Election. Tempo Magazine also presents moral values and solutions in which Prabowo's camp must accept the results of a quick count of a number of institutions survey conducted scientifically.